Development of a digital literacy program for the University of the Philippines Diliman Main Library - Macapugay, Joylyn G.; Dar Juan, Elijah John F. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2015)
This study sought to build a digitally literate community through the library and its services. Digital literacy is a relatively new concept compared to the many other types of literacies that are identified today. Digital literacy encompasses other literacies such as information literacy, ICT literacy, and computer literacy. The academic community is the perfect environment to learn the different types of literacies. Academic institutions that are fortunate to have the latest equipment such as computers, can effectively create an environment that can support digital literacy given that these institutions are also equipped with the proper learning resources such as frameworks and learning modules.
This generation is accustomed into using digital resources taken from the Internet and the World Wide Web. Although the usage of such resources comes as an advantage, people are presented with the challenge to successfully locate and select reliable resources from the vast collection of websites downloadable books, journals, and other electronic resources. Other than that, there are now different gadgets that may be used to access these resources. Technology has also greatly influenced our lifestyles. The usage of different types of social networking sites has influenced the way people work and play. In the academic setting, these social networking sites can be used to collaborate with other researchers and students alike.
The University of the Philippines Diliman Main Library holds an extensive collection of print and non-print material. Other than holding a vast subscription of information resources, the library also serves as a guide on how to properly utilize these resources. Through having a digital literacy program, libraries and other academic institutions can provide a means to enhance learner skills. The construction of the program learning modules makes use of the data gathered from students from different academic clusters of the University of the Philippines Diliman. These clusters are the Arts and Letters cluster, Management and Economics cluster, Social Sciences and Philosophy cluster, and the Science and Technology cluster. The study found out that the student respondents have different study habits when conducting online research and when evaluating resources. Their research practices and study habits can become important factors as to how they will respond to the many changes and advancements brought about by technology. These finding were used by the researcher in creating the learning modules for the program.
The library, as an academic institution's heart of information, can help students become digitally literate by providing them with an environment that fosters learning through various types of digital media. Libraries must also consider using the digital environment to promote their services and show students that libraries can keep up with the norm.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Literacy programs -- Philippines -- Quezon City; Electronic information resources